2018
DOI: 10.1002/cplu.201700501
|View full text |Cite
|
Sign up to set email alerts
|

CF3 Substitution of [Cu(P^P)(bpy)][PF6] Complexes: Effects on Photophysical Properties and Light‐Emitting Electrochemical Cell Performance

Abstract: Herein, [Cu(P^P)(N^N)][PF6] complexes (P^P=bis[2‐(diphenylphosphino)phenyl]ether (POP) or 4,5‐bis(diphenylphosphino)‐9,9‐dimethylxanthene (xantphos); N^N=CF3‐substituted 2,2′‐bipyridines (6,6′‐(CF3)2bpy, 6‐CF3bpy, 5,5′‐(CF3)2bpy, 4,4′‐(CF3)2bpy, 6,6′‐Me2‐4,4′‐(CF3)2bpy)) are reported. The effects of CF3 substitution on their structure as well as their electrochemical and photophysical properties are also presented. The HOMO–LUMO gap was tuned by the N^N ligand; the largest redshift in the metal‐to‐ligand charg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 48 publications
(128 citation statements)
references
References 37 publications
14
109
0
Order By: Relevance
“…The first oxidation of [Cu(BnN‐xantphos)(N ^ N)][PF 6 ] is significantly lower in potential than previously reported for analogous xantphos‐containing complexes. [ 30 ] This is consistent with the former being BnN‐xantphos ligand‐centered while the latter are metal‐centered. The absorption spectra of the [Cu(BnN‐xantphos)(N ^ N)][PF 6 ] compounds have been interpreted with the aid of TD‐DFT calculations.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The first oxidation of [Cu(BnN‐xantphos)(N ^ N)][PF 6 ] is significantly lower in potential than previously reported for analogous xantphos‐containing complexes. [ 30 ] This is consistent with the former being BnN‐xantphos ligand‐centered while the latter are metal‐centered. The absorption spectra of the [Cu(BnN‐xantphos)(N ^ N)][PF 6 ] compounds have been interpreted with the aid of TD‐DFT calculations.…”
Section: Discussionsupporting
confidence: 76%
“…This effect was already observed for similar series of Cu complexes. [ 29,30 ] Therefore, more negative reduction potentials are expected along both series of complexes. Regarding the highest‐occupied molecular orbital (HOMO), it is calculated at ‐6.00 eV for [Cu(xantphos)(bpy)] + and mainly resides over the metal atom with some extension to the neighboring phosphorus atoms (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the same authors proposed to use another family of Cu(I) complexes bearing different N ‐heterocyclic carbenes and dipyridylamine ligands–, i.e., di‐iso‐propylphenyl)imidazole‐2‐ylidene and 2,2ʹ‐bis‐(3‐methylpyridyl)amine, showing an effective TADF emission that led to the first blue‐emitting Cu(I)‐iTMC LECs . Other studies by Zhang et al, Bolink and co‐workers, and Costa and co‐workers showed green‐ and yellow‐emitting Cu(I)‐iTMC based devices by changing the pattern substitution of heteroleptic diamine and diphosphine ligands.…”
Section: Introductionmentioning
confidence: 99%